Is There an Association between Temporomandibular Disorders and Articular Eminence Inclination? A Systematic Review - Xiao-Chuan Fan; Diwakar Singh; Lin-Sha Ma; Eva Piehslinger; Xiao-Feng Huang; Xiaohui Rausch-Fan (Diagnostics, 2020)
(1) Background: In order to determine the correlation between the inclination of articular eminence (AEI) and the development of temporomandibular disorders (TMDs), a systematic review was performed. (2) Methods: A systematic literature research was conducted between 1946 and January 2020, based on the following electronic databases: PubMed, Cochrane Library, Embase, Medline, Scope, SciELO, and Lilacs. Observational studies, analytical case-control studies, and cohort studies written in English were identified. The articles were selected and analyzed by two authors independently. The PICO format was used to analyze the studies and the Newcastle-Ottawa Scale (NOS) was used to verify the quality of the evidence. (3) Results: Sixteen articles were included in this review, ten case-control studies and six cohort studies. Eight articles (50%) established a positive relation between AEI and TMDs and eight (50%) did not. The scientific quality was medium-low, mainly influenced by the exposure to the risk of bias and the lack of clinical methods with adequate consistency and sensitivity on the diagnosis of TMDs. (4) Conclusions: It is controversial to establish a causal relationship between the TMDs and the AEI in the field of stomatology, due to limited and inconclusive evidence. However, it is suggested that the AEI defined by some specific methods may be associated with some special pathological stages of TMDs. High-quality prospective studies are required to draw any definitive conclusions.